Brain drain as a function of sustainable development in the Republic of Macedonia - Dinkovski, Vladimir; Markovska-Simoska, Silvana (Industrija, 2018)
The main aim of this paper is research on the phenomenon “brain drain”, in the Republic of Macedonia and its impact on sustainable development. It occurs when a highly skilled, educated professionals permanently emigrates from a developing to a developed countries. The paper gives an overview of the current situation regarding the emigration of highly skilled individuals from our country and generally from the Balkans. In connection with this, we analyze how it affects the process of transition and the labor market in these countries comparing to the countries of the European Union. Research methodology was conducted by using detailed questionnaires, which were answered by students at several public and private Faculties in Macedonia. It can be concluded that the impact of brain drain on sustainable development in Republic of Macedonia and the current situation of brain drain in our country are alarming, so it deserves special attention. Applying measures to diminish the